Scientific Writing Training for Elementary School Teachers, Jaka Sanga Teacher Working Group, Karanganyar Regency - Hutami, Winanda Santi; Veronika Unun Pratiwi (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
This service was carried out to improve the skills of writing scientific papers for SD KKG Jaka Sanga teachers, Karanganyar Regency. It is time for teachers to have the ability to write scientific papers which can ultimately be published in journals or proceedings. Not understanding the stages in writing scientific work is quite worrying. Thus, this service is very important to be carried out, especially by the Indonesian Language Education Master's Study Program, Veteran Bangun Nusantara Sukoharjo University Postgraduate Program as a study program that has a concentration on language and literature development, as well as in terms of education. These service partners are teachers at SD KKG Jaka Sanga, Karanganyar Regency, who do not yet have the ability to write scientific articles or scientific works that are suitable for publication in journals/proceedings, so it is necessary to provide training in scientific writing skills. Developing skills in writing scientific papers to be able to publish them in a journal or proceedings is very necessary for instructors or teachers to improve their competence. Activities in this training can be divided into stages, namely: embedding information (encoding), integrating information into understanding (decoding), recording information (storing), training information through simulations (rehearsal), and learning information (learning). Based on the flow of the method above, it can be concluded that the method for implementing this activity includes: lecture, practice, simulation, and use of creative materials. Keywords: Training, Writing, Scientific Work, Publications, Teacher